Risk Arbitrage in Takeovers - Cornelli, Francesca; Li, David D. (Review of Financial Studies, 2002)
This article studies the role of risk arbitrageurs in takeovers and the source of their advantage. We show how the presence of arbitrageurs affects the value of the target shares, since arbitrageurs are more likely to tender. Therefore an arbitrageur has the informational advantage of knowing he bought shares. In equilibrium, the number of arbitrageurs buying shares and the price they pay are determined endogenously. We also present several empirical implications, including the relationship among trading volume, takeover premium, liquidity of the shares, and the number of risk arbitrageurs investing in one particular deal.